Pollution De L'eau De Consommation Humaine Et Risques Sanitaires A Court Terme : Cas Du Bassin Versant De La Menoua (Ouest-Cameroun) - Santsa Nguefack Charles Vital; Ndjouenkeu Robert; Ngassoum Martin Benoît (European Scientific Journal, ESJ, 2018)
The health risk associated with the consumption of water polluted by humans in the World, particularly in Africa, is a real public health problem. This is why WHO, from its inception in 1948, has always been concerned with defining limit values. The aim of this work was to study the physicochemical and microbiological quality of water in the Menoua watershed through a spatiotemporal dynamics to assess its degree of anthropogenic pollution and to estimate the level of risk of infection and diseases inherent in its consumption. Physicochemical analysis (pH, temperature, turbidity and dissolved oxygen) and microbiological (E-coli, salmonella and shigellas) was carried out on 132 samples taken from 33 sites distributed in two seasons, two in dry seasons and two in rainy season. The results show that these waters have an acidic pH, a low dissolved oxygen content, strong microorganism levels all correlated with high turbidity. These very high levels of microorganism, illustrate well the effect of the action of the man on the pollution of the water. This pollution could have several origins, the most important of which are related to spilled household discharges, without any prior treatment in rivers, manure from livestock and used in agriculture. The level of microbiological risk is very high for consumers and typhoid is the most recurrent waterborne disease in the region. This diagnosis would help decision-makers to better pronounce on the management of this resource in order to reduce the health risks inherent in its consumption.